Permeability of Borders, Ideas and Spaces - Husar, Sila Ceren Varis; Mehan, Asma; Husar, Milan; Ceylan-Caliskan, Rumeysa; Erkan-Ocek, Ruya; Song, Saebom; Leemans, Sophie (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
The world and its inhabitants are undergoing rapid transformations, including changing patterns of economic activity, more considerable societal challenges and severe environmental crises. As a subject of change, spatial planning needs to adapt effectively by thinking beyond grand urban visions and narratives. Will the planning strategies and visions of the future be well-suited to the evolving needs of communities and the paradigms of today's world? Where does the next generation of spatial planners fit into this way of thinking? This article highlights the significance of a more flexible and context-sensitive approach in spatial planning today and in the future.In this exploration, permeability is a multi-dimensional concept integral to spatial futures and planning. It involves the dynamics of physical and policy mobilities, cross-border interactions, and the search for innovative solutions to environmental and climate challenges. The discussion also emphasizes open dialogues on migration and mobility, highlighting planning values such as diversity, inclusivity, democratic accountability, rule of law and citizen engagement (AESOP 2024). Additionally, it addresses the need for pedagogical innovation in planning education to equip future planners with the necessary knowledge, skills, and understanding of the ever-changing dynamic world. Building upon the previous discussion of what comes next for planners (Var & imath;& scedil; Husar et al. 2023), this discussion contributes to a more profound critique of the merits and demerits of future-oriented planning that lie ahead primarily for the European continent. As Europe continues to shape its future, the voices and perspectives of new generation planners are essential in navigating the path towards permeability in the spatial futures.
Keywords: URBAN; CITIES; Public Administration